Modeling the long-term persistence of neutralizing antibody in children and toddlers after vaccination with live attenuated Japanese encephalitis chimeric virus vaccine - Alain Bouckenooghe; Fabrice Bailleux; Emmanuel Feroldi (Taylor & Francis Group, 2019)
The live-attenuated Japanese encephalitis chimeric virus vaccine JE-CV (IMOJEV®, Sanofi Pasteur) elicits a robust antibody response in children, which wanes over time. Clinical efficacy is based on a correlate of protection against JE infection defined as neutralizing antibody levels equal to or greater than the threshold of 10 (1/dil). Information on the duration of persistence of the JE antibody response above this threshold is needed. We constructed statistical models using 5-year persistence data from a randomised clinical trial (NCT00621764) in children (2-5 years old) primed with inactivated JE vaccine who received a booster dose of JE-CV, and in JE-naïve toddlers (12-24 months) who received a JE-CV single dose primary vaccination. Models were constructed using a Bayesian Monte-Carlo Markov Chain approach and implemented with OpenBugs V3.2.1. Antibody persistence was predicted for up to 10 years following JE-CV vaccination. Findings from a piecewise model with 2 phases (children) and a classic linear model (toddlers) are presented. For children, predicted median antibody titers (77 [2.5th-97.5th percentile range 41-144] 1/dil) remained above the threshold for seroprotection over the 10 years following booster JE-CV vaccination; the predicted median duration of protection was 19.5 years. For toddlers, 10 years after JE-CV primary vaccination median antibody titers were predicted to wane to around the level required for seroprotection (10.8 [5.8-20.1] 1/dil). A booster dose of JE-CV in children is predicted to provide long-term protection against JE. Such data are useful to facilitate decisions on implementation of and recommendations for future vaccination strategies.